Improving the knowledge of diabetes mellitus patients through health education and leaflet media in Pekaroa Village, Sawa District, North Konawe Regency - Hilda Harun; Jusniar Rusliafa; Nurmaladewi Nurmaladewi; Arum Dian Pratiwi (Indonesian Journal of Health Science, 2026)
Diabetes Mellitus (DM) is a chronic disease that constitutes a major global and national public health problem, with a continuously increasing prevalence and the potential to cause serious complications if not properly managed. One of the key factors in DM management is patients’ level of knowledge, which plays an important role in shaping self-care behaviors and adherence to therapy. This study aimed to analyze the improvement in knowledge among patients with Diabetes Mellitus regarding disease management through health education and leaflet-based media in Pekaroa Village, Sawa District, North Konawe Regency. This study employed a quasi- experimental design using a one-group pre-test and post-test without control group. The population as well as the sample consisted of all patients with Diabetes Mellitus in Pekaroa Village, totaling 8 individuals. The intervention consisted of health education accompanied by the distribution of educational leaflets on Diabetes Mellitus management. Knowledge was measured before the intervention (pre-test), after the first educational session (post- test 1), and after reinforcement of education (post-test 2). Data were analyzed using the wilcoxon signed ranks test. The results showed that the mean knowledge score increased from 2.50 (SD 0.756) at pre-test to 4.38 (SD 0.744) at post-test 1 and reached the maximum score of 5.00 at post-test 2. The wilcoxon test indicated a statistically significant difference between the pre-test and post-test 1 (p = 0.016), while the difference between post-test 1 and post-test 2 was not statistically significant (p = 0.059), although it demonstrated a trend toward improvement and stabilization of knowledge. It can be concluded that health education, reinforced by the distribution of leaflet media, is effective in improving the knowledge of patients with Diabetes Mellitus regarding the management of their disease. Educational leaflets are recommended as a simple, practical, and easily applicable educational strategy in rural communities to support Diabetes Mellitus control.